Photodegradation of methylene blue using crystalline titanosilicate quantum-confined semiconductor - Luca, Vittorio (2006)
Synthetic sitinakite contains in its structure a discrete wire-like sublattice of linked TiO6 octahedra. This sublattice is held apart by silicate tetrahedra forming one-dimensional channels that run down the c axis. The optical properties of this structural arrangement have been studied and compared with other titanosilicate phases, the best known being ETS-10. Thus, sitinakite which has twice the titanate wire diameter of ETS-10 has a band gap of 4.07 eV compared with 3.87 eV. The reduced electron-hole effective mass of the sitinakite quantum-confined system has been calculated through use of the effective mass model and compared with that of other titanosilicate materials. The sitinakite phase has been shown to effectively photodegrade methylene blue (MB) dye at pH 7 using visible light excitation and displays a higher degradation rate than TiO2 (Degussa, P25) under the same experimental conditions. On the contrary, under UV excitation, the photodegradation rate obtained using P25 is much higher than that using sitinakite. Given that the band edge of sitinkaite is significantly blue shifted compared with that of P25, photodegradation of MB using sitinakite is attributed to sensitization of the MB cationic dye which is strongly adsorbed onto the negatively charged sitinakite surfaces.